2003
DOI: 10.1152/ajpheart.00954.2002
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in EDHF-type relaxation and phosphodiesterase activity in mesenteric arteries from diabetic rats

Abstract: Matsumoto, Takayuki, Tsuneo Kobayashi, and Katsuo Kamata. Alterations in EDHF-type relaxation and phosphodiesterase activity in mesenteric arteries from diabetic rats. Am J Physiol Heart Circ Physiol 285: H283-H291, 2003; 10.1152/ajpheart.00954.2002.-In isolated superior mesenteric artery rings from age-matched control rats and streptozotocin (STZ)-induced diabetic rats, we investigated the role of cAMP in endothelium-derived hyperpolarizing factor (EDHF)-type relaxation. The ACh-induced EDHFtype relaxation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
115
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 70 publications
(112 reference statements)
13
115
1
1
Order By: Relevance
“…4), and 5) ACh increased the level of 6-keto-prostaglandin F1α in the effluent from the perfused kidneys of diabetic rats (Kamata and Hosokawa, 1997b). In the present study, an impairment of ACh-induced vasodilation was seen in the perfused kidneys of STZ-induced diabetic rats, as previously reported for other vessels in this diabetic model (Kamata et al, 1989;Kamata and Kobayashi, 1996;De Vriese et al, 2000b;Kobayashi et al, 2000;Matsumoto et al, 2003aMatsumoto et al, , 2004bKamata et al, 2005). This is in agreement with previous reports both by us (Kamata and Hosokawa, 1997b;Kamata and Hayashi, 1999;Kamata and Yamashita, 1999) and by others (Dai et al, 1993;Yousif, 2003), but in contrast to reports by Bhardwaj and Moore (1988), Gebremedhin et al (1989) and Alabadi et al (2001) who reported enhanced endothelium-dependent vasodilation of the renal vascular bed to ACh in experimentally induced diabetes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…4), and 5) ACh increased the level of 6-keto-prostaglandin F1α in the effluent from the perfused kidneys of diabetic rats (Kamata and Hosokawa, 1997b). In the present study, an impairment of ACh-induced vasodilation was seen in the perfused kidneys of STZ-induced diabetic rats, as previously reported for other vessels in this diabetic model (Kamata et al, 1989;Kamata and Kobayashi, 1996;De Vriese et al, 2000b;Kobayashi et al, 2000;Matsumoto et al, 2003aMatsumoto et al, , 2004bKamata et al, 2005). This is in agreement with previous reports both by us (Kamata and Hosokawa, 1997b;Kamata and Hayashi, 1999;Kamata and Yamashita, 1999) and by others (Dai et al, 1993;Yousif, 2003), but in contrast to reports by Bhardwaj and Moore (1988), Gebremedhin et al (1989) and Alabadi et al (2001) who reported enhanced endothelium-dependent vasodilation of the renal vascular bed to ACh in experimentally induced diabetes.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, evidence has accrued to suggest Correspondence to: Katsuo Kamata, Ph.D., Department of Physiology and Morphology, Institute of Medicinal Chemistry, Hoshi University, Shinagawa-ku, Tokyo 142-8501, Japan Phone: that EDRFs other than NO may contribute to the vascular actions of ACh (Triggle et al, 2003;Matsumoto et al, 2004a;Tanaka et al, 2004). It is well appreciated that ACh stimulates the endothelial production of vasodilatory prostaglandins (Salom et al, 1991;Majid and Navar, 1992;Vizioli et al, 2005), and current evidence suggests that an endothelium-derived hyperpolarizing factor (EDHF) may also contribute to the vasodilator actions of ACh (Busse et al, 2002;Chen et al, 1988;Matsumoto et al, 2003aMatsumoto et al, , 2003bMatsumoto et al, , 2005Matsumoto et al, , 2006aMatsumoto et al, , 2006bTakano et al, 2005;Yamamoto and Suzuki, 2005). Thus, EDRFs distinct from NO may mediate part of the ACh-induced vasodilation.…”
Section: Introductionmentioning
confidence: 99%
“…Although an accumulating body of evidence indicates that endothelium-dependent relaxation is weaker both in a type I diabetic model, namely the streptozotocin (STZ)-induced rat (Oyama et al, 1986;Kamata et al, 1989aKamata et al, , b, 1996aKamata et al, ,b,c, 1997Abiru et al, 1990a, b;Miyata et al, 1992a,b;Tomlinson et al, 1992;Poston and Taylor, 1995;Pieper, 1998;De Vriese et al, 2000;Makino et al, 2000Makino et al, , 2002Matsumoto et al, 2003Matsumoto et al, , 2004Kobayashi et al, 2004c), and in type II diabetic rats (Sakamoto et al, 1998;Walker et al, 1999;Kagota et al, 2000;Sandu et al, 2000;Kim et al, 2002;Witte et al, 2002;Matsumoto et al, 2004;Kobayashi et al, 2004c), we and others have noted an augmented or unaltered endothelium-dependent relaxation at an early stage in STZdiabetes (Brands and Fitzgerald, 1998;Pieper, 1999, Kobayashi and Kamata, 1999a, Kobayashi et al, 2005b. Moreover, there is some clinical and experimental evidence of augmented blood flow at early stages of diabetes (Jaap and Tooke, 1995;Cipolla et al, 1996; Abbreviations: ACh, acetylcholine; Ang II, angiotensin II; L-Arg, L-arginine; BH4, tetrahydrobiopterin; DOCA, deoxycorticosterone acetate; eNOS, endothelial NO synthase; ET-1, endothelin-1; GSK, glycogen synthase kinase; HDL, high density lipoprotein; HSP, heat-shock protein; IGF-1, insulin-like growth factor 1; IP3, inositol 1,4,5,-triphosphate; IRS-1, insulin receptor substrate-1; LDL, low density lipoprotein; NE, norepinephrine; NO, nitric oxide; NOS, NO synthase; PDK, PI-dependent kinase; PI3-K, phosphatidylinositol 3-kinase; PIP3, phosphatidylinositol-3,4,5-trisphosphate; PTEN, phosphatase and tensin homolog; STZ, streptozotocin; VEGF, vascular endothelial growth factor.…”
Section: Endothelium-dependent Relaxation In Diabetic Modelsmentioning
confidence: 99%
“…Cell cultures exposed to high glucose levels have been used to study gap junctions and specific connexins in isolation, with results showing attenuation of gap junction activity in bovine aortic endothelial and smooth muscle cells [22,23]. Furthermore, investigations using animal models of type 1 diabetes have shown attenuation of EDHF-mediated responses [24] and gap junction activity in mesenteric [25] arteries from streptozotocin (STZ)-induced diabetic rats. To our knowledge, no studies in insulin-resistant or type 2 diabetic animal models have studied changes in gap junction and connexin activity.…”
Section: Introductionmentioning
confidence: 99%